1997
DOI: 10.1111/j.1399-3054.1997.tb01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of oxidative stress defense systems in rice (Oryza sativa) leaves with supplemental UV‐B radiation

Abstract: 1997. Response of oxidative stress defense systems in rice {Oryza sativa) leaves with supplemental UV-B radiation. -Physiol. Plant. 101: 301-308.The impact of elevated ultraviolet-B radiation (UV-B, 280-320 nm) on membrane systems and lipid peroxidation, and possible involvement of active oxygen radicals was investigated in leaves of two UV-B susceptible rice cultivars {Oryza sativa L. cvs IR74 and Dular). Rice seedlings were grown in a greenhouse for 10 days and then treated with biologically effective UV-B (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 48 publications
4
89
0
1
Order By: Relevance
“…Because DNA and RNA polymerases are not able to read through these photoproducts, their elimination by CPD photolyases is essential for DNA replication and transcription (Britt and May 2003). UV-B exposure has been shown to increase reactive oxygen species (ROS) indicating that oxidative stress occurs (Arnott and Murphy 1991;Dai et al 1997). On the other hand, cells and tissues protect themselves against oxidative insults through the up-regulation of a wide variety of antioxidants enzymes (Davies 1986).…”
Section: Introductionmentioning
confidence: 98%
“…Because DNA and RNA polymerases are not able to read through these photoproducts, their elimination by CPD photolyases is essential for DNA replication and transcription (Britt and May 2003). UV-B exposure has been shown to increase reactive oxygen species (ROS) indicating that oxidative stress occurs (Arnott and Murphy 1991;Dai et al 1997). On the other hand, cells and tissues protect themselves against oxidative insults through the up-regulation of a wide variety of antioxidants enzymes (Davies 1986).…”
Section: Introductionmentioning
confidence: 98%
“…In response to the inevitable exposure to deleterious UV-B radiation, plants have evolved UV-induced protection and repair mechanisms, i.e., accumulation of UV-absorbing pigments and photoreactivation, utilizing blue/UV-A photons to repair most UV-B-induced DNA damages (Björn and McKenzie 2008). UV-B also stimulates antioxidant defenses (Jansen et al 1998) and production of reactive oxygen species (ROS) (Dai et al 1997). It has been suggested that the ROS can function not only as destructive radicals, but also as UV-B signaling molecules (Mackerness et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, enhanced freeradical oxygen scavenging-capacity to control oxidative damage incurred from UV-B radiation is also thought to contribute to UV-B tolerance (Elastner 1982). Dai et al (1997) indicated that UV-B-induced injury might be associated with active oxygen species in rice. Nearisogenic lines for the QTLs detected in this study should be developed to characterize their association with UV-B absorbing compounds, with photolyase activity and with active oxygen species.…”
Section: Resultsmentioning
confidence: 98%
“…A sizable number of reviews have appeared during the last two decades highlighting the effects of UV-B on plants (Teramura 1983;Allen et al 1998;Tevini and Teramura 1989;Mackerness 2000;Searles et al 2001;Hollósy 2002). Although differences in UV-B resistance have been observed in rice (Oryza sativa L.) varieties (Teramura et al 1991;Dai et al 1992Dai et al , 1997Kumagai and Sato 1992; Barnes et al 1993;Sato and Kumagai 1993), the genetic control mechanism for UV-B resistance has not been well elucidated yet.…”
Section: Introductionmentioning
confidence: 98%